Character evolution of the benthic thecate dinoflagellate, gambierdiscus (Dinophyceae), with an introduction of the interactive key to species - Nurin Izzati, Mustapa; Sing, Tung Teng; Toh, Hii Tan; Hong, Chang Lim; Po, Teen Lim; Chui, Pin Leaw (Malaysian Abstracting and Indexing System, 2015)
The genus Gambierdiscus is one of the benthic marine dinoflagellates that are known to produce biotoxins, causing ciguatera food poisoning (CFP) in humans after consuming the contaminated marine fishes. These benthic marine dinoflagellates are commonly found in the warm tropical and subtropical waters. The phenomena associated with high cell abundance or “blooms” is referred to Benthic Harmful Algal Blooms (BHABs). Precise species identification is crucial as not all of the species in the genus are toxic. In this study, morphological characteristics of Gambierdiscus species widely used in species identification were analyzed, and the character states coded. Taxon sampling on the large subunit (LSU) rDNA of all Gambierdiscus species were carried out, and used for the phylogenetic reconstruction. The character states were mapped onto the Maximum Parsimony (MP) tree to investigate the character state evolution of Gambierdiscus species. Morphological information and the distribution of the 13 species were used to develop a comprehensive taxonomic database of Gambierdiscus, a web-based interactive identification key for species identification is presented.